Gut-on-chip devices as intestinal inflammation models and their future for studying multifactorial diseases - Taavitsainen, Susanne; Juuti-Uusitalo, Kati; Kurppa, Kalle; Lindfors, Katri; Kallio, Pasi; Kellomäki, Minna (Frontiers in Lab on a Chip Technologies, 2024)
Inflammatory bowel disease (IBD), celiac disease, and other inflammatory conditions of the gastrointestinal tract are highly prevalent in society. Due to the complexity of factors involved, detailed pathogenesis is difficult to determine and thus remains elusive in many cases. The advent of gut-on-chip devices has permitted more accurate modeling of the gut microenvironment with the inclusion of fluid flow and mechanical cues that are true to intestinal architecture and physiology. This review outlines the evolution of gut-on-chip platforms towards greater physiological relevance and elucidates how these devices have been used to model and study intestinal inflammation in humans. In addition, we identify key elements from both technological and disease standpoints that are integral for accurate gut-on-chip models of IBD and celiac disease.